Upaya Pencegahan Perceraian Berbasis Keluarga Luas dan Institusi Lokal dalam Masyarakat Minangkabau di Sumatera Barat - Fachrina Fachrina; Putra Rinaldi Eka (Antropologi Indonesia, 2013)
Advisory Board Disputes Divorce dan Marriage (BP4) established government as part of effortsto reduce the divorce rate. But divorce continues from time to time and quantitatively increasingevery year, with a variety of result / impact there of. Prevention and mitigation of the problem of divorce can not be left to government officials just because the problem is multidimensional; social, cultural and moral. To overcome this problem must involve all the elements and social institutions in the local community.Keywords: Divorce, extended family, local institutions